Biochemical properties and substrate specificity of GOB-38 in Elizabethkingia anophelis - Ren Liu; Yang Liu; Jiehui Qiu; Qun Ren; Chunping Wei; Dejin Pan; Jianglong Shi; Peng Liu; DanDan Wei; Tianxin Xiang; Na Cheng (Scientific Reports)
Abstract The novel pathogen, Elizabethkingia anophelis, has gained attention due to its high mortality rates and drug resistance facilitated by its inherent metallo-β-lactamases (MBLs) genes. This study successfully identified and outlined the functions of the B3-Q MBLs variant, GOB-38, in a clinical sample of E. anophelis. The T7 expression system was employed to stimulate the expression of recombinant protein in Escherichia coli, followed by an analysis of the biochemical properties of purified GOB-38. Our findings indicate that the enzyme GOB-38 displays a wide range of substrates, including broad-spectrum penicillins, 1–4 generation cephalosporins, and carbapenems, potentially contributing to in vitro drug resistance in E. coli through a cloning mechanism. It is important to highlight that GOB-38 exhibits a distinct active site composition compared to GOB-1/18, featuring hydrophilic amino acids Thr51 and Glu141 at both ends of its active center instead of hydrophobic alanine, potentially indicating a preference for imipenem. Furthermore, the co-isolation of Acinetobacter baumannii and E. anophelis, two opportunistic pathogens, from a single lung infection is noteworthy. Our in vitro co-culture experiments suggest that E. anophelis, carrying two MBL genes, may have the ability to transfer carbapenem resistance to other bacterial species through co-infection.